Pengawasan Kawasan Sempadan Pantai: Studi Kasus 5 Wilayah Di Indonesia - Ferdiansyah Putra manggala; Johanes Saut Martua Sihombing; Nurul Laili Fadhilah (Program Studi Magister Hukum Universitas Malikussaleh, 2026)
Indonesia, as an archipelagic country, has a vast coastal area rich in natural resources. However, in practice, coastal areas that should be protected are often misused for business interests, such as the construction of shrimp farms, hotels, and resorts that do not comply with regulations. This study aims to determine how the government supervises activities in coastal areas and the legal consequences for businesses that violate these regulations. The method used is normative juridical research with a legislative approach and case studies. Based on the discussion, five cases of coastal zone violations were found in various regions such as Jember, Labuan Bajo, East Sumatra, Berau, and Takalar. These violations caused damage to the coastal environment, loss of livelihoods for the community, and disruption of the marine ecosystem. The results of the study show that government supervision is still weak, and most businesses have not been subject to strict sanctions even though the regulations are clearly stipulated in Law Number 1 of 2014 and Government Regulation Number 13 of 2017. Strict law enforcement and increased public awareness are needed so that the function of the coastal zone as a protected area can be maintained and encourage a balance between economic development and environmental sustainability.